Type 2 Ring-Opening Reactions of Cyclopropanated 7-Oxabenzonorbornadienes with Carboxylic Acid Nucleophiles - Carlson, Emily; Hong, Daniel; Tam, William (Synthesis, 2016)
Ring-opening reactions of strained heterocyclic compounds provide efficient routes to various organic frameworks. In this work, the ability of carboxylic acid nucleophiles to promote ring-opening of cyclopropanated 7-oxabenzonorbornadienes was investigated. Reactions proceeded smoothly to yield 2-naphthylmethyl esters in moderate yields, and optimal conditions were found with the use of 10 mol% p-toluenesulfonic acid monohydrate in dichloroethane heated to 90 °C. The amount of nucleophile could be decreased from a large excess to 8 equivalents without diminishing the yield. When varying the structure of the acid catalyst or carboxylic acid nucleophile, reaction rates showed a marked dependence on acidity of these species. Ring-opening was well tolerated by functionalized substrates, with substitution on the bridgehead or aromatic portions of the molecule. The present work is the second account of this type of reaction, and provides a new route to 2-naphthylmethyl esters. The transformations observed in this work should be useful in predicting the reactivity of similar fused-ring systems.
Keywords: 7-oxabenzonorbornadiene; cyclopropane; ring-opening; fused-ring systems; acid catalysis